2011
DOI: 10.1149/1.3596556
|View full text |Cite
|
Sign up to set email alerts
|

Progress in In Situ X-Ray Tomographic Microscopy of Liquid Water in Gas Diffusion Layers of PEFC

Abstract: Water management is an important factor for optimizing polymer electrolyte fuel cells (PEFC) under high current density conditions as required for the automotive application. The characteristics of the local liquid saturation of the gas diffusion layer (GDL) is of particular interest. Here we report on the development of in-situ X-ray tomographic microscopy (XTM) with a pixel sizes in the order of 2 μm and sensitivity for carbon and liquid water for the quantitative analysis of liquid water in GDLs. In-situ XT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
167
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(173 citation statements)
references
References 42 publications
6
167
0
Order By: Relevance
“…At least a two-channel design is required to obtain saturation and water distribution data over a channel & rib repetition unit without boundary bias, as it is the case in a single channel cell (Eller et al 28 ). Two different flow field designs, differing only in the rib width (0.8 and 1.6 mm) were used (see Figure 2).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At least a two-channel design is required to obtain saturation and water distribution data over a channel & rib repetition unit without boundary bias, as it is the case in a single channel cell (Eller et al 28 ). Two different flow field designs, differing only in the rib width (0.8 and 1.6 mm) were used (see Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, and different to Ref. 28, the dry XTM dataset were filtered with an inhouse implementation of the local normalization filter 38 which allows to remove the inhomogeneous background intensity within the GDL domain. The filter was applied in 2D for the in-plane (IP) direction to remove the CL patterns and in through-plane direction to remove the gradient of the gray levels from the CL toward the flow field.…”
Section: Xtm Imaging and Data Processingmentioning
confidence: 99%
“…[43][44][45][46][47][48]51,56,61,62,[64][65][66][67]71 Using XCT for membrane analysis is more challegning given the relatively low X-ray attenuation of the polymer. Garzon et al 68 demonstrated that Pt redistribution from the electrodes into the membrane can be captured by XCT.…”
mentioning
confidence: 99%
“…As the hydrostatic pressure of water increases the water will penetrate into the pores of the GDL. Previous analyses of water penetration have generally assumed uniform pores in the GDL with complex connectivity [20][21][22][23][24]. Figure 10 presents an alternative type of pore structure where the pores have variable diameters along their length.…”
Section: Water Penetration Through the Gdlmentioning
confidence: 99%
“…They suggested that liquid water only penetrates a few large pores and the smaller pores, that comprise the majority of the pore volume, remain free of liquid water and allow gas to be transported from the gas flow channel to the catalyst layer. Other researchers have employed NMR and neutron scattering imaging to confirm that liquid water penetrates only the largest pores [22][23][24]. The incipient water penetration results indicate that the tail of the pore size distribution is critical for controlling water transport.…”
Section: Introductionmentioning
confidence: 99%